Perancangan Meja Potong Kayu Menggunakan Metode TRIZ di Laboratorium Sistem Produksi Politeknik ATI Makassar - Nurwahidah, Andi; Chrisdianto , Dedy (Jurnal Industri dan Teknologi Samawa, 2025)
The Production System Laboratory at Politeknik ATI Makassar has a practical module that utilizes wood as raw material, necessitating supporting facilities such as a safe and ergonomic cutting table. The current cutting table is rudimentary, consisting of a table with a hole in the middle to accommodate the cutting machine blade. Although this setup facilitates the cutting process, it lacks protective or safety features, increasing the risk of workplace accidents. Additionally, the absence of a measuring tool on the table leads to inaccuracies in product dimensions, often resulting in student projects failing to meet the required specifications. To address these issues, the laboratory has acquired a new cutting machine. However, this machine does not come with a suitable table for its placement. Therefore, this study aims to design and develop a cutting table that enhances workplace safety while incorporating a precise measurement system. The Theory of Inventive Problem Solving (TRIZ) method is employed to identify problems and develop an optimal cutting table design. The findings indicate that the proposed cutting table design meets the requirements of the practical module and is expected to reduce the risk of workplace accidents while improving cutting accuracy